RELIGIOSITY IN ART INSPIRED BY SAMUAN TIGA AND TEJAKULA, BALI: UNITY IN DIVERSITY - Butler, Diane Carol; Ardika, I Wayan; Sedyawati, Edi; Parimartha, I Gde (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2011)
At the dawn of this third millennium, growing numbers of forums worldwide are focused on the issue of how to sustain the diversity of the nature and of cultures for the well-being of the Earth and humanity. Concurrently, intercultural and interreligious dialogue is deemed essential for social cohesion. This dissertation advances the contributions of religiosity in art through a qualitative reflective account and chronicle of the art and dialogues offered by people of diverse cultures and faiths from 1999 to 2004 during Sharing Art & Religiosity in the vicinity of Pura Samuan Tiga in Bedulu, Bali and Sharing Art Ocean– Mountain at the seacoast village of Tejakula, North Bali; seen in tandem with creative transformations that occurred through Sharing Art in and with other cultural environments of the world. Methodologically this study stemmed from and demonstrates the merits of public participatory practice-based art programs whereby activities are conceived by and implemented with the people of a locale. Participants generated the data and interpretations via mutual cooperation, dialogue, and creative praxis. The Balinese principle of Tri Hita Karana, that aims toward a harmonious human-nature-God/Source of Life relationship in accord with the place-time-conditions, provided a holistic perspective to analyze and derive meaning from the results. Findings indicate sharing in the arts, religiosity, and nature fosters a common field such that traditional and modern cultures can study and engage in creative dialogue together. Moreover, interreligious innovations that have continued to develop since the seminal deliberation of reconciliation between Bali Aga, Çiwaist, and Buddhist faith groups at Samuan Tiga circa CE 989 to 1011 and intercultural egalitarian innovations since the seventeenth century dialogue of indigenous and migrant mountain and maritime cultures in Tejakula – constitute a model for furthering bhinneka tunggal ika unity in diversity in the world today. Recommendations outline how the findings can be used for cooperative exchanges between villages and between villages and cities of diverse regions and countries to support interculture in cultural environments. Appendices provide two video compact discs; seventy- nine reflective essays by artists, religious/spiritual leaders, scholars, and educators from across the world; and nine transcriptions of initial public dialogues.